"Networked" Revolutions? ICTs and Protest Mobilization in Non-Democratic Regimes. (December 2021) - Anderson, Ashley
Despite the wealth of research linking Internet-based communication technologies (ICTs) with the rise of anti-government demonstrations in non-democracies, empirical evidence on the impact of ICTs on protest remains inconclusive. Using data from the sixth-wave of the World Values Survey (WVS), I test the relationship between ICT use and protest in non-democracies, finding that although Internet use helps to explain protest participation, organizational networks remain crucial for mobilizing protesters, even in the digital age. Notably, I find that active membership in formal organizations (i.e., attending meetings, holding leadership positions, etc.) significantly increases the likelihood of individual protest participation, providing members with the skills necessary for political engagement and connections to a sustained flow of information about protest events. Most important, I find significant interactive effects between organizational membership and ICT use—while Internet use increases the likelihood of protest engagement for all individuals, the effects of ICT use are greatest for multiply-engaged citizens who are actively involved in both online and offline organizational networks. This work thus illuminates a largely overlooked symbiosis between online and offline communities and forces a reconsideration of the ways in which organizations work to mobilize contention under authoritarian rule.